Piccole imprese in cerca dell’ eccellenza: il caso Villa Massa - Mele, Cristina; Russo Spena, Tiziana (Piccola Impresa / Small Business, 2009)
Small enterprises’ development is not correlated only to a dimensional growth, describedby traditional structural (employees) or economic (revenue) parameters, but it can be betterdefined by several indicators, able to grasp a qualitative improvement.The qualitative perspective about firm’s growth moves the focus of analysis on theexistence of excellence conditions with reference to markets, products, processes andnetworks. In this perspective the application of methodologies linked to the culturalmovement of Total Quality Management (TQM) is a valid approach to understand businessgrowth patterns.The article analyses an experience of business growth, obtained through TQM adoption.A case study was carried out on a small enterprise, producing liquors – Villa Massa – winnerof the European Excellence Award in 2007, one of the most prestigious European awards.Villa Massa’s commitment towards TQM is analysed through the nine criterias of EFQMmodel.The quality orientation integrating both cultural and operational aspects sets up the firmas value creator. Villa Massa puts into practice TQM focusing on all the firm’s stakeholdersand conceiving quality as a value creating process in a network view.